Experiences of Family Planning Acceptors Utilizing Contraceptive Implants at Hj. Dewi Sesmera’s Independent Midwifery Practice, Medan, 2024 - Miskah Indah; Fitriana Ritonga; Ninda Chairunnisa (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2025)
The continuously increasing population remains a major challenge for countries worldwide, particularly developing nations. Indonesia is a developing country with the fourth largest population in the world, after China, India, and the United States. Based on the 2015 census data, Indonesia’s population reached 238,518,000 and was projected to increase to 271,066,000 by 2020. Long-Acting Reversible Contraception (LARC), including subdermal contraceptive implants, is highly effective in preventing pregnancy. However, the utilization of LARC remains relatively low. The low uptake of Long-Term Contraceptive Methods (LTCM) is often associated with various factors, such as limited knowledge about contraceptive methods, concerns regarding side effects, discomfort, and the husband’s desire to have additional children. Therefore, this study aimed to explore the reasons, perceived benefits, and complaints experienced by contraceptive implant users at the Independent Midwifery Practice of Hj. Dewi Sesmera, Tanjung Mulia, Medan, in 2024. This research employed a qualitative approach with a phenomenological design. The informants, selected for triangulation purposes, consisted of 10 women who were family planning acceptors at the Independent Midwifery Practice of Hj. Dewi Sesmera in Tanjung Mulia, Medan. The findings revealed that implant acceptors obtained information through counseling sessions and direct communication with previous implant users. They demonstrated adequate knowledge regarding the insertion procedure and potential side effects of the implant. The factors influencing the selection of contraceptive implants included their effectiveness in long-term pregnancy prevention and spousal support. In conclusion, contraceptive implant acceptors demonstrated sufficient knowledge, effective information-seeking strategies, and identified long-term pregnancy prevention as the primary reason for choosing the implant method.